Enhanced cortical reperfusion protects coagulation factor XII-deficient mice from ischemic stroke as revealed by high-field MRI - Pham, Mirko; Kleinschnitz, C.; Helluy, X.; Bartsch, Andreas J.; Austinat, M.; Behr, V. C.; Renné, T.; Nieswandt, B.; Stoll, G.; Bendszus, Martin (NeuroImage, 2010)
Intrinsic coagulation factor XII deficient (FXII−/−) mice are protected from ischemic stroke. To elucidate underlying mechanisms we investigated the early ischemic period in vivo by multimodal magnetic resonance imaging (MRI) at 17.6 Tesla. Cerebral ischemia was induced by either transient (60 min) or permanent occlusion of the middle cerebral artery (t/pMCAO). 10 FXII−/− mice underwent t- , 10 FXII−/− mice p- and 10 Wildtype (Wt) mice tMCAO. Cerebral blood flow (CBF), diffusion-weighted-imaging (DWI) and T2-relaxometry were measured at 2 h and 24 h after MCAO. Outcome measures were evaluated after motion correction and normalization to atlas space. 2 h after tMCAO CBF reduction was similar in FXII−/− and Wt mice extending over cortical (CBF (ml/100 g/min) 33.6±6.9 vs. 35.3±4.6, p=0.42) and subcortical regions (25.7±4.5 vs. 31.6±4.0, p=0.17). At 24 h, recovery of cortical CBF by +36% was observed only in tMCAO FXII−/− mice contrasting a further decrease of -30% in Wt mice after tMCAO (p=0.02, F(1,18)=6.24). In FXII−/− mice in which patency of the MCA was not restored (pMCAO) a further decrease of −75% was observed. Cortical reperfusion in tMCAO FXII−/− mice was related to a lower risk of infarction of 59% vs. 93% in Wt mice (p=0.04). Subcortical CBF was similarly decreased in both tMCAO groups (Wt and FXII−/−) relating to a similar risk of infarction of 89% (Wt) vs. 99% (FXII−/−, p=0.17). Deficiency of FXII allows neocortical reperfusion after tMCAO and rescues brain tissue by this mechanism. This study supports the concept of FXII as a promising new target for stroke prevention and therapy.
Online verfügbar: 1. Dezember 2009
Gesehen am 03.05.2023